2020
DOI: 10.1021/acs.jchemed.9b01184
|View full text |Cite
|
Sign up to set email alerts
|

Local and Timely Class Project Promotes Student Engagement in a Nonmajors’ Course: Organic Chemistry at the North Carolina State Fair

Abstract: As a means to encourage student engagement and satisfaction in a large introductory organic chemistry class, students were tasked with the creation of instructional posters relating an organic compound to the North Carolina State Fair. Students had the freedom to choose what compound to represent and how to connect this compound to the state fair, as long as the final product was a digital poster suitable for sharing with other class members, and targeted to an audience of fair-goers. This report details the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Similar to previous studies, , students reported favorable perceptions of the infographic project, with the majority indicating they would like to see similar projects implemented in future laboratory courses. Positive perceptions that students reported include it being enjoyable, engaging, and less demanding than writing a paper.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Similar to previous studies, , students reported favorable perceptions of the infographic project, with the majority indicating they would like to see similar projects implemented in future laboratory courses. Positive perceptions that students reported include it being enjoyable, engaging, and less demanding than writing a paper.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, due to positive student feedback and recent literature indicating that student-created visual representations of target information increases engagement and the ability to communicate with diverse audiences, we incorporated student-generated infographics about green chemistry into the first semester of an organic chemistry laboratory to promote these student learning objectives (SLOs):…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemistry courses for nonmajors are important curricular contributions as they play a key role in improving scientific literacy of undergraduates . Nonmajors chemistry courses give instructors opportunities to explore creative use of themes, and published examples include use of art, food chemistry, medicinal chemistry, , and popular culture. Additional reports detail successful pedagogical approaches used in nonmajors courses, such as community outreach, , innovative projects, learning communities, and travel components. ,,, While most published work focuses on face-to-face courses, teaching nonmajors in a fully online course can allow for greater flexibility for both students and instructors, especially when taught asynchronously. Laboratory projects can be completed at home through such approaches as preassembled kits, household chemicals, and simulations. Additional creative approaches no doubt were developed in early 2020 when instructors had to quickly pivot from face-to-face classrooms and laboratories to remote delivery, and readers are encouraged to consult the Journal for additional suggestions.…”
Section: Institution and Course Backgroundmentioning
confidence: 99%
“…After examining team capabilities and successful ideas from previous virtual events conducted by other well-known organizations, the Board recognized the most daunting challenge would be the creation of a meaningful poster session experience. Poster sessions have been a critical part of scientific conferences and symposia since the 1970s. Early career researchers typically have the most to gain from this practice, because of both the educational benefits as observed at the classroom level and the exposure afforded by the opportunity to present their research to others in the scientific community. Coveted speaking spots at conferences are more difficult to come by due to prestige and logistics, so poster sessions allow a space for less established researchers to still engage others on their research. However, the large size of many conferences can introduce limitations to the value of the poster session for the individual researcher. Often the sheer number of posters outstrips any individual’s ability to visit all posters while also engaging with the rest of the conference in a limited period of time. This means few people really get to interact with these visually appealing and succinct expressions of research.…”
Section: Introductionmentioning
confidence: 99%